The new politics of home housing, gender and care in times of crisis - Jupp, Eleanor ca. 20./21. Jh; Bowlby, Sophie 1944-; Franklin, Janet 1959-; Hall, Sarah Marie ca. 20./21. Jh (Policy Press, 2019)
Setting out both new empirical material and new conceptual terrain, this book draws on approaches from human geography, social policy, and feminist and political theory to explore issues of home and care in times of crisis
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Keywords: Housing / Great Britain; Social service / Great Britain; Crises; Soziale Situation; Wohnungspolitik; Sozialarbeit; Great Britain / Social conditions; Großbritannien